Problem of Collectivization in Baltic Republics in Soviet Historiography of 1940-1960 - E. N. Kananerova (Научный диалог)
The article highlights the achievements of the Soviet historical science of 1940-1960 in the study of the problem of collectivization in the Baltic republics. The novelty of the study lies in the fact that the author for the first time made a review of Soviet historical literature on collectivization in the Baltic republics, in terms of modern scientific positions. The author considers the Soviet historical paradigm, identifies the factors of its formation, erosion and crisis in 1970-1980, which leads to the reconstruction of scientific schools, including national ones, in 1990-2000. The relevance of the study is linked, on the one hand, with the understanding of the experience of the development of historical science and the way it passed in the 20th century, on the other - with the need at the present stage to study collectivization in the Western republics and regions after the Great Patriotic war in regard to the growing contradictions in the post-Soviet space, the breeding ground for which is the tendentious use of facts from the history of the USSR. The analysis reveals the achievements of the Soviet historical science of 1940-1960 (distinguishing stages, factors and methods of collectivization) and poorly studied problems (purpose of collectivization, methods and scale of peasant resistance, number and fate of dispossessed, presence and nature of violations during the continuous collectivization and “dekulakization”).